CASPR2 autoimmunity in children expanding to mild encephalopathy with hypertension - Syrbe, Steffen; Stettner, Georg M.; Bally, Julien; Borggraefe, Ingo; Bien, Corinna I.; Ferfoglia, Ruxandra Iancu; Huppke, Peter; Kern, Jan; Polster, Tilman; Probst-Müller, Elisabeth; Schmid, Silvia; Steinfeld, Robert; et al. (Neurology, 2020)
OBJECTIVE: To delineate autoimmune disease in association with contactin-associated protein 2 (CASPR2) antibodies in childhood, we reviewed the clinical phenotype of children with CASPR2 antibodies. - METHODS: Retrospective assessment of patients recruited through laboratories specialized in autoimmune CNS disease. - RESULTS: Ten children with serum CASPR2 antibodies were identified (age at manifestation 18 months to 17 years). Eight children with CASPR2 antibody titers from ≥1:160 to 1:5,120 had complex autoimmune diseases with an age-dependent clinical phenotype. Two children with structural epilepsy due to CNS malformations harbored nonspecific low-titer CASPR2 antibodies (serum titers 1:80). The clinical symptoms of the 8 children with high-titer CASPR2 antibodies were general weakness (8/8), sleep dysregulation (8/8), dysautonomia (8/8) encephalopathy (7/8), neuropathic pain (7/8), neuromyotonia (3/8), and flaccid paresis (3/8). Adolescents (3/8) showed pain, neuromyotonia, and encephalopathy, whereas younger children (5/8) displayed severe hypertension, encephalopathy, and hormonal dysfunction mimicking a systemic disease. No tumors were identified. Motor symptoms remitted with immunotherapy. Mild behavioral changes persisted in 1 child, and autism spectrum disorder was diagnosed during follow-up in a young boy. - CONCLUSION: High-titer CASPR2 antibodies are associated with Morvan syndrome in children as young as 2 years. However, CASPR2 autoimmunity mimics systemic disease and hypertensive encephalopathy in children younger than 7 years. The outcome following immunotherapy was mostly favorable; long-term behavioral impairment may occur in younger children.
Gesehen am 07.09.2020